Effect of reducing cost sharing for outpatient care on children's inpatient services in Japan - Hirotaka Kato; Rei Goto (Health Economics Review, 2017)
Background: Assessing the impact of cost sharing on healthcare utilization is a critical issue in health economics and health policy. It may affect the utilization of different services, but is yet to be well understood. Objective: This paper investigates the effects of reducing cost sharing for outpatient services on hospital admissions by exploring a subsidy policy for children's outpatient services in Japan. Methods: Data were extracted from the Japanese Diagnosis Procedure Combination database for 2012 and 2013. A total of 366,566 inpatients from 1390 municipalities were identified. The impact of expanding outpatient care subsidy on the volume of inpatient care for 1390 Japanese municipalities was investigated using the generalized linear model with fixed effects. Results: A decrease in cost sharing for outpatient care has no significant effect on overall hospital admissions, although this effect varies by region. The subsidy reduces the number of overall admissions in low-income areas, but increases it in high-income areas. In addition, the results for admissions by type show that admissions for diagnosis increase particularly in high-income areas, but emergency admissions and ambulatory-care-sensitive-condition admissions decrease in low-income areas. Conclusions: These results suggest that outpatient and inpatient services are substitutes in low-income areas but complements in high-income ones. Although the subsidy for children's healthcare would increase medical costs, it would not improve the health status in high-income areas. Nevertheless, it could lead to some health improvements in low-income areas and, to some extent, offset costs by reducing admissions in these regions.
Keywords: I12; I18; J13; 330; Heath insurance; Cost sharing; Childcare; Inpatient care; Outpatient care